2014
DOI: 10.1002/mus.24056
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting echogenicity in flexor digitorum profundus–flexor carpi ulnaris: A diagnostic ultrasound pattern in sporadic inclusion body myositis

Abstract: FDP-FCU echogenicity contrast in muscle US is a sensitive diagnostic indicator of s-IBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 11 publications
3
60
0
4
Order By: Relevance
“…The low cost, ease of imaging at bedside and wide availability make ultrasound an appealing modality, particularly in cases of inflammatory and infectious muscle disease 5 6. Noto et al 7 showed that those with IBM have atrophy and increased echogenicity in the flexor digitorum profundus muscles, which is in striking contrast to the normal appearance of the adjacent flexor carpi ulnaris muscle. When compared with other inflammatory myopathies and amyotrophic lateral sclerosis, they showed statistically significant (p<0.05) differences in flexor digitorum-to-flexor carpi ulnaris comparisons in regard to subjective assessments of muscle echogenicity, quantitative assessments of muscle echogenicity and quality measures of muscle thickness.…”
Section: Discussionmentioning
confidence: 99%
“…The low cost, ease of imaging at bedside and wide availability make ultrasound an appealing modality, particularly in cases of inflammatory and infectious muscle disease 5 6. Noto et al 7 showed that those with IBM have atrophy and increased echogenicity in the flexor digitorum profundus muscles, which is in striking contrast to the normal appearance of the adjacent flexor carpi ulnaris muscle. When compared with other inflammatory myopathies and amyotrophic lateral sclerosis, they showed statistically significant (p<0.05) differences in flexor digitorum-to-flexor carpi ulnaris comparisons in regard to subjective assessments of muscle echogenicity, quantitative assessments of muscle echogenicity and quality measures of muscle thickness.…”
Section: Discussionmentioning
confidence: 99%
“…(Sekul et al, 1997) described the differential pattern of involvement of the forearm muscles, with the FDP being preferentially affected, whereas the flexor digitorum superficialis and extensor muscles are often spared even in the later stages of the disease (Figure 2), and these findings were subsequently confirmed in other studies (Phillips et al, 2001, Takamure et al, 2005. The differential involvement of the forearm muscles can also be demonstrated with ultrasound, and a contrasting pattern of echogenicity in the FDP and flexor carpi ulnaris muscles is considered to be typical of IBM (Noto et al, 2014).…”
Section: Muscle Imagingmentioning
confidence: 53%
“…However, there are clinical situations, such as botulinum toxin administration or fine wire electrode placement for physiological studies, in which it is critical for the electrode to be in the correct muscle. In addition, there are disease processes that affect specific muscles, such as the preferential involvement of the flexor digitorum profundus seen in inclusion body myositis [20,21]. Ultrasound is important for avoiding unintended complications such as puncturing nerves or blood vessels.…”
Section: Discussionmentioning
confidence: 99%